2022
DOI: 10.1007/s11748-022-01891-7
|View full text |Cite
|
Sign up to set email alerts
|

Differences in long-term survival outcomes after coronary artery bypass grafting using single vs multiple arterial grafts: a meta-analysis with reconstructed time-to-event data and subgroup analyses

Abstract: Objective We reviewed the available literature on patients with coronary artery disease undergoing isolated coronary artery bypass grafting (CABG) with either single (SAG) or multiple arterial grafting (MAG). Methods Original research studies that evaluated the long-term survival of MAG versus SAG were identified, from 1995 to 2022. The median overall survival (OS) and event-free OS were the primary endpoints. Comparison of median OS between the right inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Additionally, the type of sternal wound infection did not affect the chance of developing it. After a single internal mammary artery procedure, a significant risk reduction was shown in several other meta‐analyses that focused on either superficial or deep sternal wound infections, for example, severe wound healing disorder or mediastinitis 39–44 . Age, body mass index (BMI), ejection fraction, gender, diabetes mellitus, smoking, peripheral arterial occlusive disease and chronic renal insufficiency were the key factors separating the populations in these examinations with a single internal mammary artery and those with bilateral internal mammary arterys 8,9,12,14,17 .…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Additionally, the type of sternal wound infection did not affect the chance of developing it. After a single internal mammary artery procedure, a significant risk reduction was shown in several other meta‐analyses that focused on either superficial or deep sternal wound infections, for example, severe wound healing disorder or mediastinitis 39–44 . Age, body mass index (BMI), ejection fraction, gender, diabetes mellitus, smoking, peripheral arterial occlusive disease and chronic renal insufficiency were the key factors separating the populations in these examinations with a single internal mammary artery and those with bilateral internal mammary arterys 8,9,12,14,17 .…”
Section: Discussionmentioning
confidence: 95%
“…After a single internal mammary artery procedure, a significant risk reduction was shown in several other meta-analyses that focused on either superficial or deep sternal wound infections, for example, severe wound healing disorder or mediastinitis. [39][40][41][42][43][44] Age, body mass index (BMI), ejection fraction, gender, diabetes mellitus, smoking, peripheral arterial occlusive disease and chronic renal insufficiency were the key factors separating the populations in these examinations with a single F I G U R E 7 The effect's forest plot of the bilateral internal mammary artery compared to single internal mammary artery on sternal wound infection in pedicled preparation in personals with coronary artery bypass grafting.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study based on data from the SWEDEHEART registry showed that of the 37,520 patients who underwent first-time CABG surgery in Sweden between 2006 and 2017, 2.8% (1057) did not survive the first 6 months after surgery [3]. A 2022 meta-analysis based on data from 180,459 patients undergoing CABG showed that the median overall survival of patients undergoing CABG with multiple arterial grafting was 17.54 years, whereas the median overall survival of patients undergoing CABG with single arterial grafting was 11.63 years [4]. It should be noted that a number of perioperative factors may affect short-and long-term prognosis and survival in patients undergoing CABG.…”
Section: Introductionmentioning
confidence: 99%
“…Based on increasing evidence favoring the use of multiple arterial conduits in patients undergoing CABG [11], a "Hegelian" circle, based on the superiority of the MAG approach, is about to close, and a new one is about to open, which will examine different strategies in conduits harvesting, treatment protocols on the extent of target vessel stenosis for radial artery conduits, along with post-discharge treatment protocols.…”
mentioning
confidence: 99%